Stringent Nucleotide Recognition by the Ribosome at the Middle Codon Position - Wei Liu; Dongwon Shin; Martin Ng; Karissa Y. Sanbonmatsu; Yitzhak Tor; Barry S. Cooperman (Molecules, 2017)
Accurate translation of the genetic code depends on mRNA:tRNA codon:anticodon base pairing. Here we exploit an emissive, isosteric adenosine surrogate that allows direct measurement of the kinetics of codon:anticodon University of California base formation during protein synthesis. Our results suggest that codon:anticodon base pairing is subject to tighter constraints at the middle position than at the 5′- and 3′-positions, and further suggest a sequential mechanism of formation of the three base pairs in the codon:anticodon helix.